Funding issues and options for pharmacists providing sessional services to rural hospitals in Australia - Tan, A.; Emmerton, Lynne; Hattingh, H. Laetitia; La Caze, A. (CSIRO Publishing, 2015)
Objective: Many of Australia’s rural hospitals operate without an on-site pharmacist. In some, community pharmacists have sessional contracts to provide medication management services to inpatients. This paper discusses the funding arrangements of identified sessional employment models to raise awareness of options for other rural hospitals. Methods: Semistructured one-on-one interviews were conducted with rural pharmacists with experience in a sessional employment role (n = 8) or who were seeking sessional arrangements (n = 4). Participants were identified via publicity and referrals. Interviews were conducted via telephone or Skype for ~40–55 min each, recorded and analysed descriptively. Results: A shortage of state funding and reliance on federal funding was reported. Pharmacists accredited to provide medication reviews claimed remuneration via these federal schemes; however, restrictive criteria limited their scope of services. Funds pooling to subsidise remuneration for the pharmacists was evident and arrangements with local community pharmacies provided business frameworks to support sessional services.Conclusion: Participants were unaware of each other’s models of practice, highlighting the need to share information and these findings. Several similarities existed, namely, pooling funds and use of federal medication review remuneration. Findings highlighted the need for a stable remuneration pathway and business model to enable wider implementation of sessional pharmacist models. What is known about the topic?: Many rural hospitals lack an optimal workforce to provide comprehensive health services, including pharmaceutical services. One solution to address medication management shortfalls is employment of a local community pharmacist or consultant pharmacist on a sessional basis in the hospital. There is no known research into remuneration options for pharmacists providing sessional hospital services. What does this paper add?: Viability of services and financial sustainability are paramount in rural healthcare. This paper describes and compares the mechanisms initiated independently by hospitals or pharmacists to meet the medication needs of rural hospital patients. Awareness of the funding arrangements provides options for health service providers to extend services to other rural communities. What are the implications for practitioners?: Rural practitioners who identify unmet service needs may be inspired to explore funding arrangements successfully implemented by our participants. Innovative use of existing funding schemes has potential to create employment options for rural practitioners and increase provision of services in rural areas.